Filling the void: Peer assisted learning’s effects & acceptability in basic medical subjects using randomized control study in Islamabad - Arshia Bilal; Iffat Noreen; Asifa Afzal; Bushra Anwar; Ayesha Tayyab (Journal of the Pakistan Medical Association, 2026)
Objectives: To assess the effectiveness and acceptability of peer-assisted learning in basic science subjects among undergraduate medical students exposed to an integrated curriculum. Method: The randomised control study was conducted at Fazaia Medical College, Air University, Islamabad, Pakistan, from January to August 2023, and comprised second year medical students. One-third of the participants were included in the intervention group, while the rest were placed in the control group. A total five groups were formed, with four tutees led by one tutor in each group. For five weeks, a two-hour weekly session was carried out as part of the intervention by the tutors in gastrointestinal tract and Nutrition module (GIT&Nut module). The post module exam scores of the two groups were compared to assess the effectiveness of peer-assisted learning. Post-intervention feedback questionnaire was distributed to the intervention group to assess its acceptability in basic sciences. Data was analysed using SPSS 23. Results: Of the 102 students 97(95%) students had mean age 20±1 years, 67(70%) were females. Mean score in the target module of intervention group was higher (58.9±25.4) than controls (45.6±29.9), but the result was not significant (p=0.14). Feedback indicated that more than two-third 58(75%) of the participants recognised peer-assisted learning as effective and easy strategy (p<0.001). Conclusions: Peer-assisted learning was found to be an effective learning strategy by majority of the students despite showing no significant improvement in the scores of the interventional group. Key Words: Peer groups, Adult learning, Academic performance, Active learning, Curriculum.